Analysis of the chemical composition of ultrafine particles from two domestic solid biomass fired room heaters under simulated real-world use. (February 2017) - Ozgen, Senem; Becagli, Silvia; Bernardoni, Vera; Caserini, Stefano; Caruso, Donatella; Corbella, Lorenza; Dell'Acqua, Manuela; Fermo, Paola; Gonzalez, Raquel; Lonati, Giovanni; Signorini, Stefano; Tardivo, Ruggero; et al.
Abstract: Two common types of wood (beech and fir) were burned in commercial pellet (11.1 kW) and wood (8.2 kW) stoves following a combustion cycle simulating the behavior of a real-world user. Ultrafine particulate matter (UFP, dp  < 100 nm) was sampled with three parallel multistage impactors and analyzed for metals, main water soluble ions, anhydrosugars, total carbon, and PAH content. The measurement of the number concentration and size distribution was also performed by a fourth multistage impactor. UFP mass emission factors averaged to 424 mg/kgfuel for all the tested stove and wood type (fir, beech) combinations except for beech log burning in the wood stove (838 mg/kgfuel ). Compositional differences were observed for pellets and wood UFP samples, where high TC levels characterize the wood log combustion and potassium salts are dominant in every pellet sample. Crucial aspects determining the UFP composition in the wood stove experiments are critical situations in terms of available oxygen (a lack or an excess of combustion air) and high temperatures. Whereas for the automatically controlled pellets stove local situations (e.g., hindered air-fuel mixing due to heaps of pellets on the burner pot) determine the emission levels and composition. Wood samples contain more potentially carcinogenic PAHs with respect to pellets samples. Some diagnostic ratios related to PAH isomers and anhydrosugars compiled from experimental UFP data in the present study and compared to literature values proposed for the emission source discrimination for atmospheric aerosol, extend the evaluation usually limited to higher particle size fractions also to UFP. Graphical abstract: Highlights: Ultrafine particle (dp < 100 nm) chemical constituent emission factors are provided. Automatic and manually fed room heaters with two wood types are investigated. Tests conducted with appliances working under real-world operating conditions. Increased emissions (UFP, NOx, CO) for increased fuel ash content in the wood stove. PAH fingerprint shifts towards more carcinogenic PAH in wood stove UFP.